Preparation method of ionic metal organic framework and rare earth separation application

By preparing the ionic metal organic frame material ATZ-BTC-Zn, the problem of difficulty in separation and enrichment of rare earth elements in rare earth tailings or waste is solved, and efficient adsorption of light rare earth ions and separation of adjacent rare earth elements is achieved. Have good application prospects.

CN119505269APending Publication Date: 2025-02-25NANCHANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411676431.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently separate and enrich rare earth elements, especially in rare earth tailings or waste materials, where rare earth elements exist with non-lanthanide competitive ions, and similar physical and chemical properties increase the difficulty of separation.

Method used

Prepare an ionic metal organic frame material ATZ-BTC-Zn, by reacting 4-amino-4H-1,2,4-triazole, homotribenzoic acid and Zn(NO3)2·6H2O under specific conditions. A three-dimensional porous structure with open nanotrap pockets and efficient ion transport channels is formed.

Benefits of technology

This material can selectively adsorb light rare earth ions in the presence of interference ions and heavy rare earth ions, improve the diffusion and adsorption efficiency of rare earth ions, and achieve efficient enrichment of rare earth elements and separation of adjacent rare earth elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505269A_ABST
    Figure CN119505269A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an ionic metal organic framework and rare earth separation application, and belongs to the technical field of resource recovery. According to the method, the three-dimensional ionic metal organic framework material is prepared, and a large number of open type nano trap pockets composed of carboxyl and amino which are not coordinated exist in the framework and are matched with rare earth ions in size. The three-dimensional frame structure can also provide an efficient ion transmission channel, and diffusion of rare earth ions in holes can be accelerated. In addition, counter cations Zn (H2O) 6 < 2 + > in the framework and lanthanide hydrated ions are subjected to ion exchange, diffusion of rare earth ions in pore channels is further promoted, the utilization rate of effective adsorption sites is increased, and the separation effect on rare earth is enhanced. The three-dimensional ionic metal organic framework synthesized by the method has good application potential in the aspects of rare earth enrichment and separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of an ionic metal organic framework and rare earth separation application, belonging to the technical field of resource recovery. Background Art

[0002] Rare earth elements (REEs) usually exist in the form of mixed minerals, and single rare earth elements rarely exist in nature. REEs are widely used in high-tech fields such as electronic communications, new energy, defense industry, catalytic chemical industry, etc., which directly affect the country's industrial competitiveness and economic security. They must be separated and purified to meet the high purity demand for rare earths in different fields (Zhang, N., Salzinger, S., Deubel, F., Jordan, R., Rieger, B. Surface-initiated group transfer polymerization mediated by rare earth metal catalysts, J. Am. Chem. Soc., 2012, 134, 7333). The market demand and uses of different rare earth elements vary significantly. For example, neodymium (Nd) and praseodymium (Pr) are used in high-performance magnets, while europium (Eu) and terbium (Tb) play an important role in the display and lighting fields. High-purity rare earth materials are key raw materials for the development of cutting-edge technologies such as quantum computing, optical communications, aerospace, and new energy materials. By separating and purifying specific rare earth elements, not only can their economic value be maximized, but also the efficient utilization of resources can be promoted (Hu, Y., Florek, J., Larivière, D., Fontaine, F.-G., Kleitz, F. Recent advances in theseparation of rare earth elements using mesoporous hybrid materials, Chem. Rec., 2018, 18, 1261). However, the global rare earth reserves are small and unevenly distributed, and separation, purification and processing are difficult. In order to meet the growing demand for rare earth elements in the emerging clean energy technology market, recovering and separating REEs from secondary resources such as tailings has become a sustainable and environmentally friendly option. However, the relevant treatment technology is still imperfect, and the rare earths and a large number of non-lanthanide competitive ions (such as Al) in rare earth tailings or rare earth wastes are not well treated. 3+ , Fe 3+The treatment of rare earth elements (REEs, etc.) is often easily overlooked, and the similar physical and chemical properties between rare earth element ions also increase the difficulty of separation. At the same time, REEs have similar ionic radius, coordination number and coordination geometry, making the separation of adjacent rare earth elements extremely challenging. At present, the recovery of REEs from rare earth tailings and rare earth wastes mainly adopts fractional crystallization, step-by-step precipitation, ion exchange, etc. (Qi, XH, Du, KZ, Feng, ML, Gao,YJ, Huang, XY, Kanatzidis, MG Layered A 2 Sn 3 S 7 1.25H 2 O (A=organiccation) as efficient ion-exchanger for rare earth element recovery, J. Am.Chem. Soc., 2017, 139, 4314). Although these methods have certain separation effects, the concentration of rare earth elements in most wastewaters is low, and there is an urgent need to develop efficient rare earth element analysis methods and enrichment materials.

[0003] Metal-organic frameworks (MOFs) with porous network structures formed by inorganic metals and organic ligands have high specific surface area and porosity, and are widely used in multifunctional adsorption and element enrichment. The adsorption efficiency of porous adsorption materials is easily affected by the morphology and functional groups of the materials. At present, there have been certain breakthroughs in the research and application of MOFs and covalent organic frameworks (COFs), but the adsorption efficiency of most materials is relatively low (Sun, HY, Liu, Y., Lin, J., Yue, ZH, Li, WA, Jin, JC, Sun, Q., Ai, YJ, Feng, ML, Huang, XY Highly selective recovery of lanthanides by using a layered vanadate with acid and radiation resistance, Angew. Chem. Int. Ed., 2020, 59, 1878). Moreover, due to the small differences in the physical and chemical properties of rare earth elements, there are no reports on the extraction of single rare earth elements or the separation of adjacent rare earth elements. Therefore, constructing MOFs with efficient ion transport channels and unique nanotrap pocket structures is of great significance for the separation and enrichment of rare earth elements and the separation of adjacent rare earth elements. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an ionic metal organic framework and its application in rare earth separation. The ionic metal organic framework material (ATZ-BTC-Zn) prepared by the method of the present invention has a large number of open nanotrap pockets (4.4 Å) composed of uncoordinated carboxyl and amino groups in the framework, which matches the size of rare earth ions. The anionic chain skeleton of ATZ-BTC-Zn is cross-linked by hydrogen bonds to form a three-dimensional framework structure, which can provide efficient ion transmission channels and is conducive to accelerating the diffusion of rare earth ions in the pores. In addition, the counter cation Zn (H 2 O) 6 2+ Ion exchange can occur with lanthanide hydrated ions, further promoting the diffusion of rare earth ions in the pores, improving the utilization rate of effective adsorption sites, and enhancing the separation effect of rare earths. The three-dimensional porous ionic metal organic framework synthesized by the method of the present invention has good application potential in rare earth element enrichment and separation of adjacent rare earth elements.

[0005] The present invention provides a method for preparing an ionic metal organic framework, comprising: 4-amino-4H-1,2,4-triazole, tris-benzoic acid, Zn(NO 3 ) 2 6H 2 O is mixed with a solvent, the temperature is raised to 135-145 °C and the reaction is carried out at a constant temperature for 70-74 h, and then the temperature is lowered to room temperature after the reaction is completed, and the obtained white solid is vacuum filtered and washed to obtain an ionic metal organic framework.

[0006] Furthermore, the 4-amino-4H-1,2,4-triazole, s-tribenzoic acid, Zn(NO 3 ) 2 6H 2 The molar ratio of O is 1:1:(1.1-1.4).

[0007] Furthermore, the temperature is raised to 140° C. in a 6-hour program, and the temperature is lowered to room temperature in a 24-hour program.

[0008] Furthermore, the solvent is composed of a mixture of acetonitrile and water in a volume ratio of 2:8.

[0009] The present invention also provides application of the ionic metal organic framework obtained by the preparation method in rare earth separation.

[0010] Furthermore, the ionic metal organic framework can selectively adsorb light rare earth ions under the condition of coexistence of interfering ions and heavy rare earth ions.

[0011] Further, the interfering ions include Na + Mg 2+ 、Al3+ , K + , Ca 2+ , Fe 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , Pb 2 + , UO 2 2+ , the heavy rare earth ions include Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ .

[0012] Furthermore, the light rare earth ion is La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ .

[0013] Furthermore, the ionic metal organic framework is capable of separating adjacent light rare earth ions.

[0014] Furthermore, the adjacent light rare earth ions include La 3+ / Ce 3+ 、Ce 3+ / Pr 3+ , Pr 3+ / Nd 3+ 、Nd 3+ / Eu 3+ ,La 3 + / Nd 3+ 、Nd 3+ / Sm 3+ .

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The ionic metal organic framework prepared by the method of the present invention has densely packed counter cations Zn(H 2 O) 6 2+ and uncoordinated carboxyl and amino groups, forming an open nano-trap pocket with strong rare earth affinity.

[0016] 2. The ionic metal organic framework prepared by the method of the present invention can be used for rare earth ion enrichment in tailings wastewater and separation of adjacent rare earth elements, and the mechanism of action between it and rare earth elements is revealed.

[0017] 3. The counter cation Zn(H) in the ionic metal organic framework prepared by the method of the present invention 2 O) 6 2+ Ion exchange with lanthanide hydrated ions promotes the diffusion of rare earth ions in the pores, improves the utilization rate of effective adsorption sites, and enhances the separation efficiency of rare earth elements.

[0018] 4. The ionic metal-organic framework prepared by the method of the present invention can be used for the enrichment of low-concentration rare earth elements and the separation of adjacent rare earth elements. It has the advantages of good selectivity, large adsorption capacity and short equilibrium time. It realizes the enrichment of rare earth elements in tailings wastewater and the separation of adjacent rare earth elements and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Figure 2 is the single crystal structure of ATZ-BTC-Zn: (a) The smallest structural unit of ATZ-BTC-Zn; (b) The structure of ATZ-BTC-Zn along the b-axis. ab Crystal structure diagram on the plane; (c) ion transport channels formed by cross-linking of ATZ-BTC-Zn anion chains; (d) ion nanotraps in ATZ-BTC-Zn form rectangular channels and interlayer nanopockets.

[0020] Figure 2 The theoretical and experimental PXRD patterns of ATZ-BTC-Zn were derived from single crystal data.

[0021] Figure 3 This is the adsorption selectivity diagram of ATZ-BTC-Zn for rare earth elements. In a solution with a rare earth element concentration of 5 ppm, an interfering ion concentration of 50 ppm, and a pH of 2.5-6.0, the distribution coefficient K of ATZ-BTC-Zn for capturing each metal ion is d value.

[0022] Figure 4 It is the adsorption isotherm diagram of ATZ-BTC-Zn for different rare earth elements with different concentrations.

[0023] Figure 5 These are the adsorption kinetics curves of ATZ-BTC-Zn for different rare earth elements with different initial concentrations.

[0024] Figure 6It is a binary adjacent rare earth element separation model and breakthrough curve, and the separation of 6 groups of adjacent rare earth elements containing two-component mixed ions. "In" and "out" represent the ratio of the original rare earth elements in the mixed solution and the ratio in the filtrate. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0027] Example 1: Preparation and characterization of ionic metal organic framework crystal materials 0.10 mmol of 4-amino-4H-1,2,4-triazole (ATZ), 0.10 mmol of tribenzoic acid (BTC), 0.10 mmol of Zn(NO 3 ) 2 6H 2 A mixed solution of 2 mL O, 2 mL acetonitrile and 8 mL ultrapure water was placed in a 25 mL reactor, the temperature was raised to 140 °C within 6 h, and the reaction was kept at 140 °C for 72 h, then the temperature was lowered to room temperature within 24 h, the obtained colorless solid was vacuum filtered, washed with ethanol and water and dried to prepare the ionic metal-organic framework crystal material ATZ-BTC-Zn.

[0028] The crystal structure of ATZ-BTC-Zn was measured using a single crystal X-ray diffractometer. Figure 1 This is the single crystal structure diagram of ATZ-BTC-Zn. Figure 1 It can be seen that ATZ-BTC-Zn is an ionic three-dimensional porous zinc-based metal organic framework. Each Zn metal center adopts a 6-coordination mode with one ATZ, two BTC, two water molecules and one Zn(H 2 O) 6 2+ Ion binding, through the infinite expansion of this minimum asymmetric unit, forms a one-dimensional anion chain framework structure ( Figure 1 a). Zn(H 2 O) 6 2+The ions are used as counterions to balance the charge of the ATZ-BTC-Zn anion framework to maintain the electrical neutrality of the material, and are arranged in a cross-helical pattern around the anion framework. Observed from the c-axis direction, these chain frameworks are cross-linked by hydrogen bonds of water molecules to form an efficient 3D network structure, thereby providing an efficient electron transfer pathway ( Figure 1 b). Due to its similar configuration to lanthanide hydrated ions, the freely moving Zn(H 2 O) 6 2+ Dispersed inside ATZ-BTC-Zn, it creates a fast transport path for ion transport ( Figure 1 c), which helps to construct ion traps during rare earth enrichment. Figure 1 d shows that ATZ-BTC-Zn has a rectangular channel with a size of 9.9 Å × 7.8 Å along the c direction. When the chain framework is cross-linked to form a channel, the uncoordinated amino and carboxyl groups on the channel wall construct an open nanotrap, which can serve as a potential adsorption site during rare earth enrichment. Observing along the a axis, it can be seen that due to the staggered stacking of the ATZ-BTC-Zn anion chains, the uncoordinated functional groups also form a uniform interlayer nanopocket (4.4 Å), which is more suitable for the size of larger light rare earth ions.

[0029] Figure 2 The theoretical X-ray single crystal diffraction (XRD) derived from the single crystal data of ATZ-BTC-Zn and the PXRD pattern collected experimentally. By comparing the theoretical XRD spectrum derived from the single crystal data and the PXRD spectrum of the ATZ-BTC-Zn crystal powder collected experimentally, it can be seen that the ATZ-BTC-Zn crystal powder collected experimentally has obvious diffraction peaks at 2θ angles of 8.13°, 10.16°, 10.71°, 12.01°, 18.69°, and 26.27°, which match the characteristic diffraction peak positions of the theoretical XRD spectrum derived from the single crystal data, indicating that the method of the present invention is used to synthesize a high-crystallinity ATZ-BTC-Zn crystal material.

[0030] Example 2: Application of ATZ-BTC-Zn in the separation of rare earths (1) Measurement of the distribution coefficient and adsorption efficiency of ATZ-BTC-Zn for rare earth elements The adsorption selectivity of ATZ-BTC-Zn for rare earth elements was investigated. 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ 、Eu 3+ , Gd3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3 + 、Tm 3+ , Yb 3+ 、Lu 3+ ) and 50 ppm interfering ions (Na + Mg 2+ 、Al 3+ , K + , Ca 2+ , Fe 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , Pb 2+ , UO 2 2+ ATZ-BTC-Zn material was added to the mixed solution of ), the suspension was stirred for 2 h, and filtered through a 0.22 μm microporous membrane; the concentration of metal elements in the filtrate was measured by inductively coupled plasma mass spectrometry (ICP-MS), and the distribution coefficients of ATZ-BTC-Zn for various metal elements were calculated ( K d ).

[0031] Figure 3 is the adsorption selectivity diagram of ATZ-BTC-Zn for rare earth elements. Figure 3 It can be seen that as the pH increases from 2.5 to 5.5, the ATZ-BTC-Zn K d The pH value increases rapidly and reaches a maximum value, and then decreases in the pH range of 5.5 to 6.0, which can be attributed to the competitive adsorption between H⁺ and Ln³⁺, which reduces the available trap sites; at higher pH values, REEs can combine with hydroxyl groups to form Ln(H 2 O) n 3+ and Ln(OH) 2+ complexes, which can be combined with [Zn(H 2 O) 6 ] 2+ Therefore, as the solution pH value increases to 5.5, the adsorption capacity of ATZ-BTC-Zn for rare earth elements and K d It gradually increases and reaches its maximum value at pH 5.5. When the pH value increases further, K d This may be due to the fact that rare earth elements are prone to precipitation / co-precipitation under weakly acidic or alkaline conditions (such as Ln(OH)2 and Ln(OH) 3 ). Therefore, the present invention selects pH 5.5 as the optimal pH value for the adsorption experiment, which is close to the pH of the rare earth tailings wastewater used in the present invention (pH 5-6). K d 3-4 orders of magnitude higher than the interfering ions, indicating that ATZ-BTC-Zn has good selectivity for capturing rare earth elements. In addition, the K d The difference is significant, indicating that REEs have the best separation selectivity at pH 5.5. K d More than 10 4 mL·g -1 The material can be considered to be an excellent adsorbent. Figure 3 Some rare earth elements K d The values ​​are as follows: K d La = 5.49 × 10 6 mL·g -1 , K d Ce = 8.24 × 10 6 mL·g -1 , K d Pr = 7.96×10 6 mL·g -1 , K d Nd =5.87×10 6 mL·g -1 , K d Sm = 2.55 × 10 6 mL·g -1 At pH 5.5, the other REEs K d Only 10 4 mL·g -1 The adsorption of REEs by ATZ-BTC-Zn was tested at pH 5.5. 3+ 、Ce 3+ , Pr 3+ and Nd 3+The capture rate of ATZ-BTC-Zn is almost 100%, while it becomes lower and lower starting from Sm, and the capture rate of non-lanthanide elements is less than 5%, indicating that ATZ-BTC-Zn has good adsorption selectivity for rare earth elements, especially for lighter REEs.

[0032] (2) Measurement of adsorption capacity and adsorption kinetics of ATZ-BTC-Zn for different rare earth elements At pH 5.5, 50 mg of ATZ-BTC-Zn was added to 50 mL of various rare earth ions (La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3 + ) solution, stirred the suspension for 2 h, and filtered through a 0.22 μm microporous filter membrane; the concentration of various rare earth elements in the filtrate was measured by ICP-MS, and the adsorption capacity of ATZ-BTC-Zn for various rare earth elements was calculated. The adsorption capacity of ATZ-BTC-Zn for rare earth elements increases with the increase of rare earth element concentration until the adsorption equilibrium state is reached. Figure 4 This is the adsorption isotherm diagram of ATZ-BTC-Zn for different rare earth elements with different concentrations. Figure 4 It can be seen that ATZ-BTC-Zn has a strong affinity for various rare earth ions (La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ ) were 262 mg·g -1 , 169 mg g -1 , 147 mg g -1 , 227 mg·g -1 , 168 mg g-1 , 167 mg g -1 , 286 mg·g -1 , 159 mg g -1 , 174 mg g -1 , 132 mg·g -1 , 177 mg g -1 , 214 mg·g -1 , 239 mg·g -1 , 182mg·g -1 .

[0033] At pH 5.5, 100 mg of ATZ-BTC-Zn was added to 100 mL of various rare earth ions (La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ 、Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ ) solution, stirred, sampled and filtered at regular intervals, the concentration of rare earth ions in the filtrate was measured by ICP-MS, and the adsorption capacity of ATZ-BTC-Zn for rare earth ions at different time points was calculated. Figure 5 is the adsorption kinetic curve of ATZ-BTC-Zn for different rare earth elements with different initial concentrations. Figure 5 It can be seen that the adsorption of various rare earth elements by ATZ-BTC-Zn reached equilibrium within 15 min, and all adsorption processes were well consistent with the pseudo-second-order model (R 2 >0.99), which is significantly faster than many existing adsorbents, indicating that ATZ-BTC-Zn has fast adsorption kinetics for various rare earth elements. The high adsorption capacity and fast adsorption kinetics of ATZ-BTC-Zn for rare earth elements can be attributed to the free movement of Zn (H 2 O) 6 2+ Dispersed inside ATZ-BTC-Zn, they create a fast transmission channel for ion transfer, which enables the uncoordinated amino and carboxyl groups on the inner wall of the three-dimensional pores of ATZ-BTC-Zn to form rare earth element-affinity ion nanotraps after the anionic chain skeleton of ATZ-BTC-Zn is cross-linked, resulting in the strong affinity and efficient enrichment ability of ATZ-BTC-Zn for rare earth elements.

[0034] Example 3: Application of ATZ-BTC-Zn in separation of adjacent rare earth elements The effect of ATZ-BTC-Zn in one-step separation of adjacent rare earth elements was investigated using adjacent rare earth elements as binary mixed ion models. 10 mg ATZ-BTC-Zn was added to a binary mixed solution containing adjacent rare earth elements (M1 and M2) in a molar ratio of 1:1. The mixed solution was shaken at 120 rpm for 30 min and filtered with a 0.22 μm nylon membrane. The concentration of rare earth ions in the filtrate was measured by ICP-MS, and the separation factor was calculated. Six groups of binary model combinations of adjacent rare earth ions were explored, including Ce 3+ / La 3+ 、Ce 3+ / Pr 3+ , Pr 3+ / Nd 3+ 、Nd 3+ / Eu 3+ ,La 3+ / Nd 3+ 、Nd 3+ / Sm 3+ . Among them, Ce 3+ / La 3+ 、Ce 3+ / Pr 3+ 、Nd 3 + / Sm 3+ The three binary model combinations were used in the breakthrough experiment of separation of adjacent rare earth elements. The three breakthrough curves showed significant differences, especially for La / 3+ Ce 3+ In these binary mixed systems, the affinity of ATZ-BTC-Zn to the adjacent rare earth elements is consistent with the selective adsorption coefficient results under thermodynamic equilibrium. Figure 6 It is the separation model and breakthrough curve of binary adjacent rare earth elements. Figure 6 It can be seen that the separation factor of ATZ-BTC-Zn for binary mixtures ( SF )Gundam SF Ce / La = 543, SF Ce / Pr =289, SF Pr / Nd = 46, SF Nd / Eu = 38, SF La / Nd = 908, SF Nd / Sm = 155, the results show that ATZ-BTC-Zn can be used to separate adjacent rare earth elements in one step. 3+ / Nd 3+The separation factor is much higher than that of the literature method (Yin, X., Wang, Y., Bai, X., Wang, Y., Chen, L., Xiao, C., Diwu, J., Du, S., Chai, Z., Albrecht-Schmitt, TE, Wang, S. Rare earth separations by selective boratecrystallization. Nat. Commun., 2017, 8, 14438). 3+ / La 3+ The separation effect is much better than that of crystallization separation (Yang, P., Zhuang, Q., Li, Y., Gu, J. Green separation of rare earthelements by valence-selective crystallization of MOFs. Chem. Commun., 2019,55, 14902).

[0035] The enrichment capacity of ATZ-BTC-Zn for rare earth elements in rare earth tailings wastewater in Ganzhou, Jiangxi Province was investigated. The content of rare earth elements and interfering ions in the tailings wastewater was tested by ICP-MS. The concentration of rare earth elements was about 0.16 to 1.23 ppm, while the content of competing ions (such as Al and Ca) in the tailings wastewater was 8.2 ppm. The breakthrough curve results of ATZ-BTC-Zn for metal ions in tailings wastewater showed that the concentration of rare earth elements and interfering ions (Na + Mg 2+ 、Al 3+ , K + , Ca 2+ , Fe 2+ 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , Pb 2+ , UO 2 2+ ) and heavy REEs ions (Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ ) compared to ATZ-BTC-Zn for light rare earth ions (La3+ 、Ce 3+ , Pr 3+ 、Nd 3+ ) has a larger adsorption capacity and breakthrough bed volume. For example, La 3+ The breakthrough curve of Pr is located at 70 breakthrough bed volumes. 3+ and Nd 3+ The breakthrough bed volumes of Ce 3+ The maximum breakthrough column volume is 200 column volumes, while other ions stop within only 10 breakthrough bed volumes, indicating that ATZ-BTC-Zn has a good selective separation effect on rare earth elements in tailings wastewater, especially adjacent rare earth elements.

[0036] It can be seen that the ionic three-dimensional porous ATZ-BTC-Zn crystal material prepared by the method of the present invention realizes the enrichment of rare earth elements and the separation of adjacent rare earth elements, can be used for the separation and enrichment of rare earth elements in rare earth tailings wastewater, and has good application prospects.

[0037] The embodiments described above only express several preferred embodiments of the present invention, and the descriptions thereof are relatively specific and detailed, but are not intended to limit the present invention. It should be noted that for those skilled in the art, the present invention may also have various changes and modifications, and any modifications, equivalent substitutions, improvements, etc. made within the concept and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an ionic metal organic framework, characterized in that: include: 4-Amino-4H-1,2,4-triazole, tris-benzoic acid, Zn(NO3)2·6H2O and a solvent are mixed, the temperature is raised to 135-145°C and the reaction is carried out at a constant temperature for 70-74 hours, and then the temperature is lowered to room temperature after the reaction is completed. The obtained white solid is vacuum filtered and washed to obtain an ionic metal organic framework.

2. The method for preparing an ionic metal organic framework according to claim 1, characterized in that: The molar ratio of the 4-amino-4H-1,2,4-triazole, tris-benzoic acid and Zn(NO3)2·6H2O is 1:1:(1.1-1.4).

3. The method for preparing an ionic metal organic framework according to claim 1, characterized in that: The temperature was raised to 140° C. over 6 h, and the temperature was lowered to room temperature over 24 h.

4. The method for preparing an ionic metal organic framework according to claim 1, characterized in that: The solvent is composed of acetonitrile and water mixed in a volume ratio of 2:

8.

5. Use of the ionic metal organic framework obtained by the preparation method according to any one of claims 1 to 4 in rare earth separation.

6. The use according to claim 5, characterized in that: The ionic metal organic framework can selectively adsorb light rare earth ions under the condition of coexistence of interfering ions and heavy rare earth ions.

7. The use according to claim 6, characterized in that: The interfering ions include Na + Mg 2+ 、Al 3+ , K + , Ca 2+ , Fe 2 + 、Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ , Pb 2+ 、UO2 2+ , the heavy rare earth ions include Sm 3+ 、Eu 3+ , Gd 3+ , Tb 3+ 、Dy 3+ 、Ho 3+ , Er 3+ 、Tm 3+ , Yb 3+ 、Lu 3+ , the light rare earth ion is La 3+ 、Ce 3+ , Pr 3+ 、Nd 3+ .

8. The use according to claim 5, characterized in that: The ionic metal organic framework is capable of separating adjacent light rare earth ions.

9. The use according to claim 8, characterized in that: The adjacent light rare earth ions include La 3+ / Ce 3+ 、Ce 3+ / Pr 3 + , Pr 3+ / Nd 3+ 、Nd 3+ / Eu 3+ ,La 3+ / Nd 3+ 、Nd 3+ / Sm 3+ .

Citation Information

Cited By

  • Method for preparing fluorine-containing metal organic framework material and recovering associated rare earth

    CN120966029A